Sustainable advertising or ecolabels: Which is the best for your brand and for consumers’ environmental consciousness? - Ferreira, Alcina Gaspar (2021)
This research contributes to the understanding of sustainable brands loyalty by evaluating con sumers’ perceptions of different communication tools. An online consumer survey collected 441 valid responses and partial least square structural equation modeling was applied to analyze data. Results reveal that ecolabels consciousness contributes to create a sustainable brand image and to develop environmental consciousness, whereas perceived advertising spend does not. Also, loyalty to sustainable brands is influenced by consumers’ environmental consciousness but not by sustain able brands image. Our findings suggest that environmental consciousness is crucial to develop sustainable brands loyalty, reinforcing the importance of consumers’ environmental education.